Hypothetical Evaluation of Stress and Displacement of the Mandible with Chin Cup Therapy Using Various Force Vectors (Finite Element Study) - Hussain A. Obaidi; Ayad A. Abdulrazak; Lomya A. Abdulrahman (University of Mosul, College of Dentistry, 2015)
Introduction: Early orthodontic treatment is recommended, since the morphologic pattern of the prognathic face associated with excessive forward mandibular growth is most likely established early in life. The chin cup is the preferred orthopedic appliance for growing children with mandibular prognathism and a normal maxilla. Aims Of Study: Evaluation of the stress and displacements in the mandible from various chin cup force vectors, using three-dimensional finite element model. Materials And Methods: Three-dimensional model of the mandible was modeled and analyzed. Chin cup with 800 g force was applied on the pogonion of the mandible. The direction of the loading vectors were 150, 200, 250, 300, 350, 400 and 900 relative to x axis, then, the mechanical responses in terms of displacement and Von Mises stresses are evaluated. Results: The highest stress levels observed in the condylar, posterior ramus regions and inferior sigmoid notch, and increased as the force vector was transferred away from the condyle. The mandible was displaced in downward and backward direction with the vector passing below and through the condyle (with angles 150, 200 and 250) forward and upward displacement was recorded as the force vector move away from the condyle (within 300, 350, 400 and 900). Conclusions: With the limitations of modeling, boundary conditions, and solution assumptions, chin cup applied in various directions produce different force vectors, which induce different stress and displacements. The force vector is an important determinant of the orthopedic effects of the chin cup and therefore should be carefully considered.